Remote education in Brazilian federal universities: challenges and adaptations of education during the COVID-19 pandemic - Mélo, Cláudia Batista (2020)
Due to the onset of Sars-Cov-2, a viral infection spread around the world, causing a pandemic. There was a need to comply with measures of social distancing, causing several sectors to interrupt their face-to-face activities. From this perspective, the academic routine was also affected, generating the need for adaptations in education, with the implementation of remote teaching, after authorization by the Ministry of Education, through Ordinance N. 544/2020. This study aims to report and discuss remote education at federal universities in Brazil. This is a descriptive, qualitative and documentary study on the characteristics of the offer of remote education. Primary data sources were used in the public domain. The population was composed of all federal universities in Brazil, totaling 69 institutions. The sample consisted of 65 institutions offering courses in the health area. Of the universities analyzed, 84.6% adopted remote education, 12.3% did not start the schedule and 3.1% did not report on their website. The pioneer universities in the access to remote education are located in the Northeast (17.7%) and Southeast (5.5%) regions, the North has the largest number of institutions that did not start the schedule (44.4%). There was no suspension of research activities (93.4%), nor extension (95.2%). The challenges resulting from COVID-19 pandemic led federal institutions to analyze teaching alternatives. Remote education was adopted by most universities as a possibility for continuity of education in the field of teaching, research and extension.